Scope 2 and market-based accounting - workshop report - Matthew Brander; Jesse Backstrom; Michael Gillenwater; Lissy Langer; Olivier Corradi; Malte Schäfer; Jon Sigvert; Ciril Wakounig; Anders Bjørn (Carbon Management)
This report summarises the presentations and discussions at an international workshop on ‘Scope 2 and Market-based Accounting’, held on 28th April 2023 at the Technical University of Denmark (DTU). There was broad agreement that the current GHG Protocol scope 2 guidance is problematic in terms of ensuring accurate GHG claims. Several presentations discussed the necessity of temporal and spatial matching of consumption and energy attributes, and an identified topic for further research is to determine the spatial boundaries of an electricity grid. Additionality was also a key issue in most of the presentations and the discussions, either as a further necessary requirement for accurate market-based accounting, or for reporting on and incentivising actions that achieve genuine real-world impact. In either case, there was agreement on the need for tests or indicators to operationalise the concept of additionality.